Solid Lipid Nanoparticle (Sln): A Modern Approach for Drug Delivery - Patel, Dilip; Kesharwani, Roohi; Nair, Suresh Kumar (Asian Journal of Pharmaceutical Research and Development, 2015)
Lipid nanoparticles were developed in the last decade of the last century as alternative carrier system to emulsions, liposomes and polymeric nanoparticles. Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) are the two main types of lipid nanoparticles. The present review focuses on the utility of SLN in terms of their advantages, production methodology, characterization and applications. Due to their unique size-dependent properties, lipid nanoparticles offer the possibility to develop new therapeutics. The ability to incorporate drugs into nanocarriers offers a new prototype in drug delivery that could be used for secondary and tertiary levels of drug targeting. Hence, solid lipid nanoparticles hold great promise for reaching the goal of controlled and site specific drug delivery and hence have attracted wide attention of researchers.